Management of giant benign fibrous histiocytoma in the spinal region with pleural involvement: A case report. Issue 39 (September 2019) - Liu, Shuzhong; Zhou, Xi; Song, An; Huo, Zhen; Yao, Siyuan; Wang, Yipeng; Liu, Yong
Abstract: Rationale: Benign fibrous histiocytoma with pleural involvement in spinal region is a highly unusual disease with no standard curative managements yet. The objective of this study is to report an extremely rare case of a giant benign fibrous histiocytoma with pleural involvement in spinal region successfully operated by posterior spinal surgery. The management of these unique cases has yet to be well-documented. Patient concerns: A 23-year-old man presented with a 2-month history of continuous and progressive back pain. A giant, expanding lesion of the T7 vertebral and paraspinal region with pleural involvement was identified. Diagnoses: Computed tomography scan and magnetic resonance imaging of spine showed expanding lesion of the T7 vertebral and paraspinal region involving the right thoracic cavity, which presented as a solid tumor. Postoperative pathology confirmed the diagnosis of thoracic benign fibrous histiocytoma. Interventions: The patient underwent thoracic spinal canal decompression, complete tumor resection, pleural defect repair, and T4 to T10 internal fixation procedure via a posterior approach. Outcomes: The patient's symptom improved significantly after the surgery, and the postoperative period was uneventful at the 2-year follow-up visit. There were no complications associated with the operation during the follow-up period. Lessons: In summary, the tumor's clinical features, imaging results, and pathological characteristics are unique. Combined efforts of specialists from orthopedics, thoracic surgery, neurosurgery, pathology, and medical oncology led to the successful diagnosis and management of this patient. Giant benign fibrous histiocytoma with pleural involvement in spinal region, although rare, should be part of the differential diagnosis when the patient presents with back pain and radiculopathy. We recommend the posterior or 1-stage anterior–posterior combined approach for complete resection of the giant thoracic benign fibrous histiocytoma when the tumor has caused severe symptoms or neurological deficits.